Cheater or mutualist? Novel florivory interaction between nectar‐rich Crotalaria cunninghamii and small mammals. (23rd December 2015) - Popic, Tony J.; Davila, Yvonne C.; Wardle, Glenda M.
Abstract: Animals visit flowers to access resources and by moving pollen to conspecific individuals act as pollinators. While biotic pollinators can increase the seed set of plants, other flower visitors can reduce seed set directly by damaging vital reproductive organs and indirectly by affecting the way the plant interacts with subsequent flower visitors. It is, therefore, vital to understand the varied effects of all visitors and not only pollinators on plant fitness, including those visitors that are temporally or spatially rare. We document the first known case of flower visitation by small mammals to C rotalaria cunninghamii (Fabaceae), a plant species morphologically suited to bird pollination. During a rain‐driven resource pulse in the Simpson Desert in 2011, the rodents M us musculus (Muridae) and P seudomys hermannsburgensis (Muridae) visited flowers to remove nectar by puncturing the calyx. We investigated the effects of this novel interaction on the reproductive output of C . cunninghamii . Compared with another recent resource pulse in 2007, plants flowering during mammal visitation had five times as many inflorescences per plant, 90% more flowers per inflorescence, and two to three times more nectar per flower, but this nectar was 30% less sugar rich. Concurrently, rodent plagues were up to three times larger during this rain‐driven resource pulse than during a previous pulse in 2007. Up to 75% of flowers had evidence of small mammal florivory, but this was not necessarily destructive, as up to 90% of fruit had the remains of florivory. Through a series of exclusion experiments, we found that small mammal florivory did not directly reduce seed set. We conclude that rain‐driven resource pulses led to a unique combination of events that facilitated the novel florivory interaction. Our findings emphasize the dynamic nature of biotic interactions and the importance of testing the role of all visitors to pollination services.